Management Information System in Public Service: A Review of Literature - Arifin Tahir; Fayzal Lamakaraka (Westscience Press, 2023)
This research aims to present the implications of management information systems in public services through literature review analysis. The method used in this research is to use a descriptive qualitative method which refers to a literature review study, where the author conducted research by analyzing various literature sources that discuss the same topic, starting from scientific journal articles, books, various other relevant literature to be used. reference. The results of this research show that management information systems have an important role in producing quality public services. Through an optimal and effective management information system, it will indirectly influence the realization of quality public services in an organization.